Outsourcing Patriarchy To and Within India: Intersectional and Decolonial Gender Politics Across Scales. Issue 3 (1st December 2020) - Gilbertson, Amanda
Abstract: Young caste‐class privileged gender justice workers in Delhi navigate several relations of power—with Euro‐American feminisms, and with less privileged feminisms and recipients of development work within India. Their experiences reveal that decolonial politics in India cannot be conceptualised without consideration of other axes of inequality including caste and religion. There is thus a need to broaden decolonial and intersectional analyses to include multiple spatial scales, from the transnational to the most granular interpretations of the local. By bringing intersectional analyses into greater dialogue with postcolonial feminist theory, this paper demonstrates that patterns of "outsourcing patriarchy" are observable at many scales, and that these patterns at different scales are co‐produced, each in turn shaping the other. Such a framework also explains how young caste‐class privileged gender justice workers outsource patriarchy and reproduce "mainstream" feminisms even as they seek to avoid doing so.